THE ISSUE OF CRAFTSMANSHIP IN THE FINANCIAL SYSTEM OF THE KOKAND KHANATE - Khatamova Zumradkhan Nazirjonovna (Scholar Express Journals, 2024)
The article analyzes the financial system of the Kokand Khanate and issues of handicrafts in its development.
Keywords: Khan; money; tax; finance